2017
DOI: 10.1002/lno.10718
|View full text |Cite
|
Sign up to set email alerts
|

Non‐seagrass carbon contributions to seagrass sediment blue carbon

Abstract: Non‐seagrass sources account for ∼ 50% of the sediment organic carbon (SOC) in many seagrass beds, a fraction that may derive from external organic matter (OM) advected into the meadow and trapped by the seagrass canopy or produced in situ. If allochthonous carbon fluxes are responsible for the non‐seagrass SOC in a given seagrass bed, this fraction should decrease with distance from the meadow perimeter. Identifying the spatial origin of SOC is important for closing seagrass carbon budgets and “blue carbon” o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
32
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 50 publications
(39 citation statements)
references
References 60 publications
6
32
1
Order By: Relevance
“…). These findings align with other studies that have found largely allochthonous contributions to seagrass sediment OC stocks, with 50% or more of the carbon originating from non‐seagrass sources such as macroalgae, salt marsh vegetation, benthic microalgae, plankton, or terrestrial sources (Kennedy et al ; Miyajima et al ; Greiner et al ; Oreska et al ). While the isotope sources used here are distinct from one another, overlapping source signatures can make it challenging to decipher relative contributions to the sediments.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…). These findings align with other studies that have found largely allochthonous contributions to seagrass sediment OC stocks, with 50% or more of the carbon originating from non‐seagrass sources such as macroalgae, salt marsh vegetation, benthic microalgae, plankton, or terrestrial sources (Kennedy et al ; Miyajima et al ; Greiner et al ; Oreska et al ). While the isotope sources used here are distinct from one another, overlapping source signatures can make it challenging to decipher relative contributions to the sediments.…”
Section: Discussionsupporting
confidence: 91%
“…Seagrasses often exhibit high rates of primary productivity, and this biomass can become incorporated into the sediment carbon pool. Seagrass canopies also facilitate particle capture and settlement from the water column, which can further enhance carbon stocks and accretion rates (Hendriks et al ; Duarte et al ; Macreadie et al ) Thus, the OC found in seagrass meadow sediments can be autochthonous—produced within a given meadow—or allochthonous—produced outside the meadow (Kennedy et al ; Miyajima et al ; Oreska et al ). The OC buried in seagrass sediments is generally subject to low rates of remineralization, as the sediments tend to be low in oxygen below the first few millimeters, resulting in reduced microbial decomposition (Fourqurean et al ; Duarte et al ; Greiner et al ).…”
mentioning
confidence: 99%
“…Our isotopic data suggest that the organic carbon that ends up in eelgrass meadow sediments is largely derived from noneelgrass sources, which aligns with previous findings that upward of 50% of carbon in seagrass sediments may be allochthonous in origin (Kennedy et al, ; Miyajima et al, ; Oreska et al, ; Prentice et al, ). While we did not have enough replicates of sediment isotope values or enough localized signatures of potential carbon sources to determine the relative proportion of carbon sources using an isotope mixing model, the biplot shows a clear separation of signatures in the sediments from those of Z. marina across various regions (Figure ).…”
Section: Discussionsupporting
confidence: 91%
“…The literature is equivocal regarding the effects of eutrophication on seagrass carbon storage and burial, reporting both higher storage and burial due to an increased input of sestonic particles (Gacia et al, 2002;Mazarrasa et al, 2017;Samper-Villarreal et al, 2017), and decreased storage and burial due to detrimental effects on seagrass productivity and survival (Macreadie et al, 2012;Jiang et al, 2018). Here, the level of eutrophication appeared to increase C stock (Figures 4C-F and Table 1), suggesting that Danish eelgrass meadows have a relatively high reliance on allochthonous carbon (Oreska et al, 2017b). In fact, for 10 of the sites used in this study, the eelgrass net primary production only explained 2.3% of the variation in C stock indicating a low contribution of autochthonous carbon (Röhr et al, 2016).…”
Section: Eutrophication Effects On Eelgrass Sediment Stocksmentioning
confidence: 93%